Management of Hemophilia in Spain - Martin-Villar, J; Ortega, F; Magallon, M (Thrombosis and Haemostasis, 1976)
Results are presented of a nation-wide inquiry into the management of hemophilia in Spain. It is calculated that there are 1,172 hemophilic patients in the country. A survey has been made of the therapeutic materials (prepared commercially or by hospitals) used in 1974 and their availability in the various hospitals of the Social Security Service. It is estimated that an average of 10,708 units of deficient factor were used per patient in this year. The number of patients on home therapy is 1.2% of the total. All cost of hemophilia treatment is covered by the Social Security. Comments are made on progress during the last five years.